Pengaruh Indeks Dow Jones, Suku Bunga The Fed, Dan Bitcoin terhadap IHSG - Saputra, Firmansyah Indra; Purwanto, Eko (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research was conducted to examine the effect of the Dow Jones Index, The Fed Interest Rate, and Bitcoin on the Indonesian Composite Stock Price Index (IHSG). The data used is secondary data taken based on closing prices and monthly fluctuations from financial websites. The population is in the form of time series data for 58 months starting from 1 June 2018 to 31 March 2023 using a saturated sample. Data analysis in the study used the classical assumption test (multicollinearity, heteroscedasticity, autocorrelation, normality), multiple linear regression, determinant coefficient, and T test. The results showed that the Dow jones index had a positive effect on the JCI, The Fed's interest rate had a positive effect on the JCI, and Bitcoin has no effect on the JCI. The test results stated that the Dow Jones Index had a positive influence on the JCI, The Fed's Interest Rate had a positive influence on the JCI, and Bitcoin had no influence on the JCI. Keywords: Bitcoins; Dow Jones; IHSG; The Fed